2005
DOI: 10.3354/dao065053
|View full text |Cite
|
Sign up to set email alerts
|

Direct identification of Photobacterium damselae subspecies piscicida by PCR-RFLP analysis

Abstract: Fish pasteurellosis is an infectious disease that affects several teleost species living in temperate marine waters. The pathogen responsible, Photobacterium damselae subspecies piscicida, shows high genetic similarity with P. damselae subsp. damselae, making subspecies discrimination extremely laborious. Here we report for the first time a PCR-RFLP method for the identification of P. damselae subsp. piscicida without prior isolation in pure culture. Genomic sequence information was obtained through cloning an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 24 publications
0
20
0
2
Order By: Relevance
“…In the last two decades efforts have been made to develop rapid and specific protocols for early detection of fish pathogens and prevent potential disease outbreaks (del Cerro et al, 2002;Romalde et al, 1999;Zappulli et al, 2005). Although these approaches proved to be appropriate for positive identification of the subspecies of P. damselae, none of them were able to perform direct simultaneous detection of both subspecies in water samples from natural or artificial systems, which limit their application in the process of disease outbreak control.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last two decades efforts have been made to develop rapid and specific protocols for early detection of fish pathogens and prevent potential disease outbreaks (del Cerro et al, 2002;Romalde et al, 1999;Zappulli et al, 2005). Although these approaches proved to be appropriate for positive identification of the subspecies of P. damselae, none of them were able to perform direct simultaneous detection of both subspecies in water samples from natural or artificial systems, which limit their application in the process of disease outbreak control.…”
Section: Resultsmentioning
confidence: 99%
“…However, these techniques are often laborious, time-consuming and lack sensitivity. In the last years, despite the high homology in the DNA sequence of both subspecies (Gauthier et al, 1995;Osorio et al, 1999), several studies developed protocols using molecular techniques to overcome the limitations of the conventional microbiological techniques and to allow the detection of P. damselae (Kvitt et al, 2002;Osorio et al, 1999;Zhao and Aoki, 1989) and distinguish the two subspecies (Amagliani et al, 2009;Zappulli et al, 2005). Previous studies showed that different genotypes of P. damselae subspecies piscicida and damselae can have different phenotypic characteristics and pathogenicity potential (Hawke et al, 2003;Takahashi et al, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…Individuals of group 1 were challenged by immersion with Photobacterium damselae subspecies piscicida (3 × 10 5 bacteria l − 1 ). Group 1 was challenged with a low virulence strain (DI21, Zappulli et al, 2005) to obtain sub-lethal infection. Group 2 was mock-infected by immersion in clean aerated seawater.…”
Section: Animals Collection and Rna Extractionmentioning
confidence: 99%
“…Tissue samples from these fishes were collected and stored as described above. A pathogen-specific test was performed on DNA extracted from infected tissues (Zappulli et al, 2005). All group 1 individuals were strongly positive for the presence of the pathogen.…”
Section: Animals Collection and Rna Extractionmentioning
confidence: 99%
See 1 more Smart Citation